2016
DOI: 10.2337/db16-0823
|View full text |Cite
|
Sign up to set email alerts
|

Antithymocyte Globulin Plus G-CSF Combination Therapy Leads to Sustained Immunomodulatory and Metabolic Effects in a Subset of Responders With Established Type 1 Diabetes

Abstract: Low-dose antithymocyte globulin (ATG) plus pegylated granulocyte colony-stimulating factor (G-CSF) preserves β-cell function for at least 12 months in type 1 diabetes. Herein, we describe metabolic and immunological parameters 24 months following treatment. Patients with established type 1 diabetes (duration 4–24 months) were randomized to ATG and pegylated G-CSF (ATG+G-CSF) (N = 17) or placebo (N = 8). Primary outcomes included C-peptide area under the curve (AUC) following a mixed-meal tolerance test (MMTT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 25 publications
1
71
1
Order By: Relevance
“…However, this follow-up study found subjects receiving ATG/G-CSF had reduced CD4 + T-cells and CD4 + /CD8 + T-cell ratio and increased natural killer cells, memory T-cells, and neutrophils (86). Additionally, Tregs were elevated after 6, 12, and 18 months, but not after 24 months (86). Taken together, these results suggest that ATG/G-CSF therapy leads to prolonged immunomodulatory effects and a larger clinical trial in recent-onset T1D is underway within the TrialNet Clinical Network (https://clinicaltrials.gov/ct2/show/NCT02215200).…”
Section: Combination Immunotherapiesmentioning
confidence: 97%
See 2 more Smart Citations
“…However, this follow-up study found subjects receiving ATG/G-CSF had reduced CD4 + T-cells and CD4 + /CD8 + T-cell ratio and increased natural killer cells, memory T-cells, and neutrophils (86). Additionally, Tregs were elevated after 6, 12, and 18 months, but not after 24 months (86). Taken together, these results suggest that ATG/G-CSF therapy leads to prolonged immunomodulatory effects and a larger clinical trial in recent-onset T1D is underway within the TrialNet Clinical Network (https://clinicaltrials.gov/ct2/show/NCT02215200).…”
Section: Combination Immunotherapiesmentioning
confidence: 97%
“…HbA1c levels also tended to be lower at 6 months in those who received ATG/G-CSF (83). A two-year follow-up revealed no difference in C-peptide levels 24 months post-intervention (86). However, this follow-up study found subjects receiving ATG/G-CSF had reduced CD4 + T-cells and CD4 + /CD8 + T-cell ratio and increased natural killer cells, memory T-cells, and neutrophils (86).…”
Section: Combination Immunotherapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination therapy with anti-thymocyte globulin and GM-CSF has been shown to increase Treg frequency, alter DC pheno-types, and improve survival in mouse models of type 1 diabetes [124,125]. This combinatorial approach was validated when explored in clinical trials of type 1 diabetics, improving Treg frequency and preserving β-cell function compared to placebo controls [126,127]. While careful consideration should be given to therapies that completely ablate leukocyte subpopulations for fear of promoting systemic immunosuppression, there is growing evidence that suggests immunoablation in combination with immunomodulation can be a useful approach.…”
Section: Future Directionsmentioning
confidence: 99%
“…In terms of human clinical trials, the vast majority have targeted adaptive immunity. G-CSF combination therapy has recently been tested in humans, where it was well tolerated 83. Both Aralast and Imatinib human T1D trials have been initiated, but the full results are not yet known 84.…”
Section: Novel Approaches To Immunotherapy For T1d: Targeting Innate mentioning
confidence: 99%